2022
DOI: 10.21203/rs.3.rs-2042255/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mnx1 Induces Leukemia Transformation Through Altering Histone Methylation in a Model of Pediatric Acute Myeloid Leukemia with t(7;12)(q36;p13)

Abstract: Certain subtypes of acute myeloid leukemia (AML) in children have still inferior outcome. One of these AML subtypes has a translocation t(7;12)(q36;p13), always leading to high expression of MNX1 and often to MNX1::ETV6 fusion expression. Here we identified the transforming event in this AML and possible ways to target them. Only MNX1 was able to induce AML in mice, and this was observed using hematopoietic stem and progenitor cells derived from fetal origin but not from adult bone marrow. The restriction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…We explored the utility of the hemogenic gastruloid model in understanding the cellular consequences of oncogenic events putatively initiated during development. We elected to investigate MNX1 -driven AML, the most common of infant-unique forms of AML, which we and others (Ingenhag et al, 2019; Ragusa et al, 2022; Waraky et al, 2022) have shown to be incapable of transforming adult cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We explored the utility of the hemogenic gastruloid model in understanding the cellular consequences of oncogenic events putatively initiated during development. We elected to investigate MNX1 -driven AML, the most common of infant-unique forms of AML, which we and others (Ingenhag et al, 2019; Ragusa et al, 2022; Waraky et al, 2022) have shown to be incapable of transforming adult cells.…”
Section: Resultsmentioning
confidence: 99%
“…Its overexpression does not result in leukemic transformation of neonatal cord blood cells or adult mouse bone marrow, but blocks erythroid differentiation and results in cellular senescence (Ingenhag et al, 2019;Waraky et al, 2022;Wildenhain et al, 2010;Wildenhain et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the MLL/ENL fusion was able to transform HSCs in serial re-plating colony-forming cell (CFC) assays, MNX1/ETV6 with or without overexpression of MNX1 did not confer self-renewal capacity. A recent pre-print has also failed to detect leukaemogenic potential of MNX1/ETV6 fusion-transduced foetal liver (FL) cells in mouse transplantation experiments [ 55 ]. However, the authors described an i n vitro myeloid differentiation bias of cells transduced with the fusion transcript.…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…However, the authors described an i n vitro myeloid differentiation bias of cells transduced with the fusion transcript. Significantly, no effects of MNX1/ETV6 were detected in adult bone marrow (BM) cells [ 55 ], hinting at the proposed in utero origins of t(7;12) leukaemia. Overall, with a MNX1/ETV6 protein still not identified, the role of the fusion transcript has remained questionable.…”
Section: Biological Mechanismsmentioning
confidence: 99%